(untitled) (Development Service Industry Management, 2025)
Risk management in business models of social enterprises is an extremely relevant area of scientific research, since modern social enterprises operate in a complex, dynamic and unpredictable environment. Unlike traditional enterprises, they combine economic goals with the implementation of a social mission, which increases the range of risks and increases the requirements for the formation of an effective and sustainable business model. Rapid changes in market conditions, fluctuations in funding sources, increased competition, limited resources, as well as the need to maintain a balance between social impact and financial performance make risk management a key element of the development of social enterprises. In addition, the role of social innovations is growing, which, despite their high potential, are accompanied by an increased level of uncertainty and require special tools for assessing and minimizing risks. Social enterprises, combining commercial activities with the implementation of a social mission, face a unique set of risks that differ both in the nature of occurrence and in the level of impact on their business model. Traditional approaches to risk management developed for commercial organizations do not always take into account the specifics of social orientation, limited resources, dependence on grant funding, volunteer work or partnerships with government and public structures. This results in many social enterprises remaining vulnerable to financial, operational, reputational, and institutional risks. Main purpose of the study is to substantiate approaches to risk management in the business models of social enterprises and to identify effective tools for their minimization, taking into account the specifics of the functioning of the social sector and the conditions of the modern market environment. To achieve this goal, it is planned to analyze theoretical approaches to the essence of social entrepreneurship and its business models, to identify the main types of risks characteristic of social enterprises, as well as to investigate their sources and consequences for the activities of the organization. In today’s economy, social enterprises play an increasingly important role as a tool for implementing social innovations, overcoming inequalities and providing access to socially significant services. Unlike traditional companies, social enterprises operate in a multidimensional environment where business logic is combined with the implementation of a social mission. Such a dual orientation forms a specific range of risks that require special approaches to management. The problems of financial instability, dependence on donor resources, variability of social demand, non-standard income models and complex interaction with stakeholders make risk management one of the key factors for the long-term viability of social enterprises. At the same time, traditional risk management methods cannot always be effectively applied in the social business sector, which necessitates their adaptation or the formation of new tools. Risk management in the business models of social enterprises is a critical element in ensuring their long-term sustainability and effectiveness. The combination of a social mission with commercial activities creates a specific set of risks that are complex in nature and require a systematic approach. Social enterprises face not only traditional financial, operational or market risks, but also social and reputational threats that can significantly affect their operations. The use of risk management tools within the business model allows you to identify potential threats in time, assess their impact and develop effective measures to minimize them. Among the most effective tools are environmental monitoring, diversification of funding sources, partnerships, staff training, implementation of quality standards and establishing transparent communication with stakeholders.